(untitled) (International journal of artificial intelligence, 2026)
This paper presents an overview of Uzbekistan’s Big Solar Furnace (BSF) in Uzbekistan, one of only two megawatt-class solar furnaces worldwide, and its role in the synthesis of functional ceramics, high-entropy alloys (HEAs), and MXene-based electrodes for hydrogen production. The BSF, with a thermal capacity of 1 MW and maximum temperatures exceeding 3,000 °C, enables clean and scalable experiments in advanced materials science. We discuss experimental achievements in oxide ceramics, antireflective coatings, molten alumina, and smart greenhouse films. In addition, MXene/NF and MXene–GO–CB/NF electrodes have shown promising results for water electrolysis, with low overpotentials, large electrochemically active surface areas, and high thermodynamic efficiencies (82–88%). The integration of solar-driven materials processing and MXene-based electrocatalysts underlines Uzbekistan’s growing role in advancing sustainable, low-carbon technologies.